Frequency jump in an ion linac - R. Duperrier; N. Pichoff; D. Uriot (Physical Review Special Topics. Accelerators and Beams, 2007)
Frequency jumps in an ion linac use to be made in order to provide a large transverse acceptance in the low-energy part and a high accelerating gradient in the high-energy part. This frequency jump may induce a discontinuity in the average longitudinal force per focusing period and shrink the longitudinal acceptance of the linac if this transition is not performed carefully. In this paper, three techniques are developed which produce a “certain” continuity of the channel at the transition between. The continuity type is discussed. It is demonstrated that the longitudinal acceptance can be preserved whatever the frequencies of the cavities in the linac. This point is very important when comparisons between different cavity types are made (spoke and elliptical cavities for, instance). A few examples are shown to illustrate the performances of the three techniques.